Quand le mieux est l’ennemi du bien : David Ross Brower, la militance environnementaliste et la prospérité matérielle - Jean-Daniel Collomb (Transatlantica)
This article addresses the vulnerability of American environmentalist discourse during the post-World War II boom: while the growing success of the environmental movement in the United States can largely be attributed to an unprecedentedly large distribution of material wealth after 1945, many environmentalists had warned Americans against the negative effects of economic growth and mass consumption. Therefore, the success of the environmental movement depended on the very socioeconomic conditions against which it was protesting, which, from a strategic perspective, meant that the end of prosperity might also undermine public appetite for environmental protection. This article analyzes the constraints this tension imposes on environmental advocacy. It takes the works of the prominent environmentalist David Ross Brower as a case study in order to address the following questions: How did Brower deal with the socioeconomic conditions of the postwar years? What constraints did those conditions impose on his advocacy? The article uses material from Brower’s papers that are held in the Bancroft Library at the University of California, Berkeley.